Improving Lecturer Well-Being through Mental Workload and Change Management Training at Universitas Negeri Surabaya: Peningkatan Kesejahteraan Dosen melalui Pelatihan Manajemen Beban Kerja Mental dan Manajemen Perubahan di Universitas Negeri Surabaya - Meita Santi Budiani; Seger Handoyo; Rahkman Ardi (Lembaga Riset dan Inovasi Masyarakat Madani, 2026)
Lecturers play a central role in higher education through teaching, research, community service, and administrative responsibilities. These multiple roles often increase mental workload and require lecturers to adapt to organizational changes, which may affect their well-being. This community service program aims to improve lecturers’ capacity to manage work pressure, respond to organizational changes, and strengthen workplace well-being. The program involved 54 lecturers at Universitas Negeri Surabaya and employed an educational-participatory approach through a workshop on mental workload and change management. The evaluation used adapted scales of occupational well-being, perceived organizational change, and trust in colleagues, supported by pre-test and post-test measurements. The results showed positive changes across the measured indicators. Scores for self-management increased from 3.3 to 4.7, changed management from 3.4 to 4.6, and well-being from 3.5 to 4.3. In addition, participants’ understanding of the material reached an average score of 4.8 out of 5.0, with satisfaction at 4.5 and perceived importance of the program at 4.7. These findings indicate that the workshop contributed positively to improving lecturers’ readiness to manage mental workload and organizational change. The program implies that universities need to provide continuous support for lecturers’ well-being through relevant and contextual capacity-building initiatives.